2015
DOI: 10.1038/tpj.2015.81
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gene polymorphims on the warfarin treatment at initial stage

Abstract: The adverse reactions of warfarin that were found mainly occurred in the first month. This study was carried out to observe the effect of gene polymorphisms on the warfarin therapy at the initial stage. Four-hundred and sixty Chinese patients began warfarin treatment with daily 2.5 mg after heart valve replacement operations were enrolled. The daily international normalized ratio (INR) for anticoagulation were recorded till the seventh day. Blood samples were collected and used to detect genotypes for VKORC1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…This variant has been reported to impact significantly on warfarin efficacy, especially at the early stages of therapy commencement, in a study of 460 Chinese patients. 17 The same study observed suboptimal INR values in about 90% of patients who were carriers of VKORC1*3 after 7 days of daily 2.5 mg warfarin administration. Another study in Sudanese subjects who had been on warfarin for at least three months showed that the mean daily dose was about 14% higher in homozygous and heterozygous VKORC1*3 carriers, 18 while variability in warfarin plasma levels and an expected adjustment of warfarin doses was also explainable by VKORC1*3 in addition to CYP2C9*8 in South Africans.…”
Section: Discussionmentioning
confidence: 87%
“…This variant has been reported to impact significantly on warfarin efficacy, especially at the early stages of therapy commencement, in a study of 460 Chinese patients. 17 The same study observed suboptimal INR values in about 90% of patients who were carriers of VKORC1*3 after 7 days of daily 2.5 mg warfarin administration. Another study in Sudanese subjects who had been on warfarin for at least three months showed that the mean daily dose was about 14% higher in homozygous and heterozygous VKORC1*3 carriers, 18 while variability in warfarin plasma levels and an expected adjustment of warfarin doses was also explainable by VKORC1*3 in addition to CYP2C9*8 in South Africans.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, the anticoagulation-effect of warfarin is somewhat delayed. Hence, patients with warfarin often have complications such as thrombosis and hemorrhage in the early stage [15][16][17]. In contrast, low molecular weight heparin or rivaroxaban usually reach peaks of blood concentration at 2-4 hours after administration [18][19][20], which may be one of the important reasons for the late onset of symptomatic PE in our research.…”
Section: Discussionmentioning
confidence: 87%
“…20-HETEs possess multifaceted effects on cardiovascular functions including those implicated to the pathogenesis of CVD: stimulation of smooth muscle contractility, migration, and proliferation, as well as activation of endothelial cell dysfunction, angiogenesis, and inflammation [ 9 , 15 ]. Cytochrome P450 4A11 and 4F2 are the major 20-HETE-producing CYP4 isoforms in humans [ 16 , 17 ] which also participate in the metabolism of several drugs including those used for therapy of CVDs [ 18 ].…”
Section: Introductionmentioning
confidence: 99%